Mechanistic insights into complement inhibition - Duan, Huiquan (My University, 2025)
The complement system is a fundamental component of innate immunity, acting as a first line of defense against pathogens, maintaining immune homeostasis, and bridging the gap between initial pathogen recognition and the adaptive immune response. It is tightly regulated to ensure efficient pathogen elimination while preventing host tissue damage. However, dysregulation of this system can lead to a range of pathologies driven by excessive or misdirected complement activation. Existing treatments have brought substantial benefits to patients with complement-mediated diseases such as paroxysmal nocturnal hemoglobinuria (PNH) and atypical hemolytic uremic syndrome (aHUS), yet limitations regarding efficiency and specificity underscore the need for novel complement inhibitors. This study explores four distinct strategies of complement inhibition that collectively aim to expand our understanding of complement modulation and provide insights into precise complement regulation and inhibitor development. The first strategy involves engineered variants of the Complement Receptor of the Immunoglobulin Superfamily (CRIg). Contrary to earlier reports of only micromolar binding affinities, we found that CRIg binds C3b and iC3b with nanomolar affinity, offering potent inhibition of the alternative pathway (AP). By depleting lysine residues and applying crosslinking modifications, we further enhanced their inhibitory efficacy, suggesting that CRIg can serve as a versatile scaffold for designing next-generation biologics with improved potency and pathway specificity. The second approach centers on synthetic DNA aptamers targeting factor B (FB), a critical protease for AP activation. These aptamers successfully neutralize multiple aHUS-associated FB mutants by disrupting their interaction with C3b, underscoring the aptamers’ capacity to address disease-causing complement genetic variants. Third, we discovered that the sandfly salivary protein SALO, a classical pathway (CP) inhibitor, binds the zymogen form of C1r with nanomolar affinity. By shielding the activation loop, SALO blocks C1r zymogen autoactivation and thereby prevents downstream C1r and C1s functions. This “zymogen-shielding” mechanism distinguishes SALO from other immune evasion proteins or therapeutic inhibitors. Lastly, we expanded our understanding of the Staphylococcus aureus virulence factor EfbC by identifying human complement factor H–related protein 2 (FHR2) as a novel target. We found that EfbC forms a ternary interaction with FHR2 and C3b, resulting in stronger inhibition of the terminal complement pathway. Collectively, these four strategies—spanning engineered human complement receptor, synthetic aptamers, arthropod-derived inhibitors, and bacterial immune evasion protein—underscore the immense therapeutic potential of fine-tuning complement at multiple points along its activation pathways. Such targeted approaches not only advance our understanding of complement biology but also offer valuable insights for developing innovative, more precise treatments for a range of complement-driven diseases.
Keywords: Complement system; Complement inhibition; Complement inhibitor; Innate immunity